Series solution to the Pochhammer-Chree equation and comparison with exact solutions - Shawagfeh, N; Kaya, D (Pergamon-Elsevier Science Ltd, 2004)
In this study, a decomposition method for approximating the solution of the Pochhammer-Chree equation is implemented. By using this scheme, explicit exact solution is calculated in the form of a convergent power series with easily computable components. To illustrate the application of this method numerical results are derived by using the calculated components of the decomposition series. The obtained results are found to be in good agreement with the exact solutions known for some special cases. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: decomposition method; Pochhammer-Chree equation; traveling wave solution; solitary wave solution